2019
DOI: 10.1111/anec.12650
|View full text |Cite
|
Sign up to set email alerts
|

When and how does a single ventricular premature beat initiate and terminate supraventricular tachycardia?

Abstract: Background:The differential diagnosis of a supraventricular tachycardia (SVT) is accomplished using a number of pacing maneuvers. The incidence and mechanism of a single ventricular premature beat (VPB) on initiation and termination of tachycardia were evaluated during programmed electrical stimulation (PES) of the heart in patients with the two most common regular SVTs: atrioventricular re-entrant tachycardia (AVNRT) and orthodromic atrioventricular tachycardia (AVRT). Methods:Three hundred and thirty-seven c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Typical AVNRT is usually inducible by atrial pacing maneuvers and uncommonly by VES 1 . Rarely, typical AVNRT can be induced only by VES and can be explained by the two different mechanisms as explained in this case.…”
Section: Resultsmentioning
confidence: 69%
“…Typical AVNRT is usually inducible by atrial pacing maneuvers and uncommonly by VES 1 . Rarely, typical AVNRT can be induced only by VES and can be explained by the two different mechanisms as explained in this case.…”
Section: Resultsmentioning
confidence: 69%
“…They found that while initiation of orthodromic atrioventricular reentrant tachycardia occurred in 34/120 (28.3%) patients by a single ventricular premature beat, initiation of typical AVNRT was observed in only 8/217 (3.6%) patients (P < .001). However, AVNRT initiation by a burst from the right ventricle is more common, because consecutive beats can more easily get into the A-V node, and was seen in 18 out of 217 (8.2%) patients (1). In this case, the QRS morphology during VT suggests activation originating in the apical part of the septum which may have facilitated retrograde impulse conduction up into the His-Purkinje system.…”
Section: Electrophysiologic Studymentioning
confidence: 88%